2020
DOI: 10.3390/brainsci10030186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Transcranial Magnetic Stimulation (rTMS) Combined with Aerobic Exercise on the Recovery of Motor Function in Ischemic Stroke Rat Model

Abstract: The therapeutic benefits of repetitive transcranial magnetic stimulation (rTMS) combined with rehabilitation therapy on recovery after stroke have not been fully elucidated. This study aimed to explore the therapeutic effects of rTMS followed by aerobic exercise on neuroplasticity and recovery of motor function in a rat model of permanent middle cerebral artery occlusion (MCAO). Rats were randomized into sham operation (N = 10, sham op), MCAO (N = 10, control group), rTMS (N = 10, MCAO and rTMS therapy), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The present results were largely supported by the findings of other groups, which demonstrated that exercise accelerated CBF (Pianta et al, 2019), decreased infarct volume (Tian et al, 2013;Pan et al, 2020) and improved functional outcomes (Pianta et al, 2019). In contrast, a few studies have reported no neuroprotective effects of exercise on the neurological deficit and infarct volume after stroke within 3 days (Matsuda et al, 2011;Cui et al, 2020). Future studies are necessary to fully elucidate the effect of post-stroke exercise on brain injury.…”
Section: Discussionsupporting
confidence: 88%
“…The present results were largely supported by the findings of other groups, which demonstrated that exercise accelerated CBF (Pianta et al, 2019), decreased infarct volume (Tian et al, 2013;Pan et al, 2020) and improved functional outcomes (Pianta et al, 2019). In contrast, a few studies have reported no neuroprotective effects of exercise on the neurological deficit and infarct volume after stroke within 3 days (Matsuda et al, 2011;Cui et al, 2020). Future studies are necessary to fully elucidate the effect of post-stroke exercise on brain injury.…”
Section: Discussionsupporting
confidence: 88%
“…The present results were further supported by the results of other groups, which indicated that various types and intensities of early exercise postconditioning accelerated CBF (Pianta et al, 2019 ), decreased infarct volume (Tian et al, 2013 ; Pan et al, 2020 ) and improved functional outcomes (Pianta et al, 2019 ). However, a few studies claimed that no obvious improvements were found after post-stroke exercise treatment on brain infarct and recovery (Matsuda et al, 2011 ; Cui et al, 2020 ). These studies employed models of 90-min ischemia or permanent MCAO models in their exercise procedures, whereas we used a model of 120 min temporary ischemia and induced a relatively small size of infarction.…”
Section: Discussionmentioning
confidence: 99%
“…This is of interest since phasic GABAergic signaling is a potential target for drug therapeutics in mice (Hiu et al, 2016). TMS combined with exercise significantly increased expression of Brain-Derived Neurotrophic Factor and TrkB after middle cerebral artery occlusion in rats (Cui et al, 2020). Hogan and colleagues have written a useful review concerning the molecular mechanisms resulting from neural stimulation and those involving neural plasticity (Hogan et al, 2020).…”
Section: Repetitive Stimulation Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%